Electrical current measurements from poised electrodes of microbial three-electrode systems from drained thaw lake basins near Barrow, Alaska, 2011-2012 - E. Friedman; L. Angenent (Arctic Data Center, 2013)
2011: Electrical current measurements from poised electrodes of microbial three-electrode systems from a young, medium, old, and ancient aged drained-thaw lake basins. At each basin there are duplicate measurements at shallow (7 centimeter (cm)), medium (10 cm), and deep (14 cm) depths below the soil surface. All current values are in micro-amperes. 2012: Electrical current measurements from poised electrodes of microbial three-electrode systems from three ice-wedge polygons within a medium aged drained-thaw lake basin. Within each polygon there are duplicate measurements at shallow (6 cm) and deep (10 cm) below the soil surface. All current values are in micro-amperes. See Friedman et al. (2012) Biosensors and Bioelectronics 32: 309-313.